A real-world disproportionality analysis of FDA Adverse Event Reporting System (FAERS) events for baricitinib. Issue 11 (1st November 2020) - Peng, Ling; Xiao, Kui; Ottaviani, Silvia; Stebbing, Justin; Wang, Ying-Jie
ABSTRACT: Background: Baricitinib is approved for the treatment of rheumatoid arthritis (RA). The authors retrospectively investigated adverse events (AEs) by data-mining a self-reporting database to better understand toxicities, especially since it has been used during the coronavirus disease 2019 (COVID-19) pandemic. Methods: A reporting odds ratio (ROR) was used to detect the risk signals from the data in the US Food and Drug Administration (FDA) adverse event reporting system database (FAERS). The definition relied on system organ class (SOCs) and preferred terms (PTs) by the Medical Dictionary for Regulatory Activities (MedDRA). Results: The search retrieved 1, 598 baricitinib-associated cases within the reporting period: 86 PTs with significant disproportionality were retained. Infections including 'herpes zoster, ' 'oral herpes, ' and 'herpes virus infection' were found at a similar rate to those reported in trials, and such events were rare. Reports emerged for several thrombotic adverse events, while these events were also rare. Unexpected safety signals as opportunistic infections were detected. Serious outcomes as death and life-threatening outcomes accounted for 9.76% of the reported cases. Conclusions: The incidence of these AEs does not appear above the background expected. These data are consistent with routine clinical observations and suggest the importance of pharmacovigilance.